Nine views of the Phillips curve: eight authentic and one inauthentic - Forder, J (University of Oxford, 2014)
There is a widely believed but entirely mythical story to the effect that the discovery of 'the Phillips curve' was, in the 1960s and perhaps later, an inspiration to inflationist policy. The point that this is a myth is argued in Forder, Macroeconomics and the Phillips curve myth, OUP 2014. One aspect of the explanation of how that myth came to be widely believed is considered in this paper. It is noted that the expression 'Phillips curve' was applied in a number of quite distinct and inconsistent ways, and as a result there was, by about 1980, an enormous confusion as to what that label meant. This confusion, as well as the multiplicity of possible meanings, it is suggested, made the acceptance of the myth much easier, and is therefore part, although only part, of the story of its acceptance.